Essays on international economics - Abreu, Ana Lucia Vahia de (2006)
This study in International Economics has three main goals. First, to indicate, among seven price indices, the one with the highest purchasing power parity (PPP) evidence; second, to suggest that the international trade theory explains to satisfaction the real exchange rate parity among countries with similar relative-factor-endowment; and third, to study the impact of the Brazilian trade openness on labor demand elasticity.